1992
DOI: 10.1002/kin.550240902
|View full text |Cite
|
Sign up to set email alerts
|

Shock tube and modeling study of propene pyrolysis

Abstract: The thermal decomposition of propene behind reflected shock waves with 1200 < Ts < 1800 K and 1.6 X mol/cm3 was studied by IR laser kinetic absorption spectroscopy and gas-chromatographic analysis of reaction products. The present data together with earlier shock tube data were satisfactorily modeled with a 51-reaction mechanism. As the initial step of the reaction, three channels, C3H6 = CH3 + CzH3 (11, C3H6 = H + AC3H5 (2), and C3H6 = CH, + CzHz (3), were necessary to interpret all the experimental data. 0 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 41 publications
4
39
0
Order By: Relevance
“…7) is another evidence for its molecular origin. This result does not disagree with those obtained by Hidaka et al [31]. They could not identify this molecular source of allene because radical routes are probably important at Instead, they 1200 -1800 K. identified a molecular elimination of methane: which might be in competition with (m 1 ) at 800 K. We failed to detect any trace of acetylene even though this hydrocarbon should be very easily detected; this suggests that Hidaka's activation energy for may k 109 be too low, or that extrapolation of their data to is impossible.…”
supporting
confidence: 71%
“…7) is another evidence for its molecular origin. This result does not disagree with those obtained by Hidaka et al [31]. They could not identify this molecular source of allene because radical routes are probably important at Instead, they 1200 -1800 K. identified a molecular elimination of methane: which might be in competition with (m 1 ) at 800 K. We failed to detect any trace of acetylene even though this hydrocarbon should be very easily detected; this suggests that Hidaka's activation energy for may k 109 be too low, or that extrapolation of their data to is impossible.…”
supporting
confidence: 71%
“…Hidaka et al [3] investigated the thermal decomposition of propene behind reflected shock waves over a temperature range of 1200-1800 K, measuring the product distribution using infrared laser absorption spectroscopy and gas chromatography. The authors reported species profiles for C 3 H 6 , C 2 H 2 , C 4 H 6 , C 3 H 4 , and C 6 H 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Note also that trans-cyclopropane-d, isomerizes to 1-d, (33). A possible explanation, put forward by Bernardi et al (34) is that "It is conceivable that the structural isomerization proceeds by a path not involving trimethylene, and hence may not be pertinent to the [1,2] shift transition state." Clearly more experimental work is needed on this problem which we are currently investigating by theoretical methods.…”
Section: Photochemical Reactions Ofmentioning
confidence: 99%
“…Pour des longueurs de liaison 1. Introduction Propene (1) has been the object of many investigations of its thermal (1)(2)(3)(4)(5)(6)(7)(8) and photochemical reactions (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), but the overall reaction mechanisms are still not fully elucidated. An important reason is the large number of products at lower pyrolysis temperatures: for instance Kallend et al (8) identified 26 products, many of which are more reactive than 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation